Frontal bone fibrous dysplasia in a 6-months-old boy: A distinctive entity - Kleanthis Anastasiadis; Vassilis Lambropoulos; Kalliopi Tsoleka; Chrysostomos Kepertis; Vassilis Mouravas; Ioannis Spyridakis (PAGEPress Publications, 2021)
Fibrous Dysplasia (FD) is a non-malignant condition caused by post-zygotic, activating mutations of the GNAS gene that results in inhibition of the differentiation and proliferation of bone-forming stromal cells and leads to the replacement of normal bone and marrow by fibrous tissue and woven bone. The clinical behavior and progression of FD is variable. The management of this condition is difficult and in every case is strictly individualized. We report a case of frontal fibrous dysplasia in a 6month's old boy who underwent a successfully resection of the lesion with an excellent cosmetic effect.